LINKING SACRED PLACEWITH NATURE: RELIGIOUS ARCHITECTURE OF TADAO ANDO AND RIDWANKAMIL - Siddiq, Akhmad (IAIN Kediri, 2018)
Contrary to common perspective of sacred place, which usually excludes nature and environment from its discourse, this paper attempts to link nature with sacred place. This paper asserts that human perspective of God does not essentially exclude humanÃ¢â‚¬â„¢s linkage with environment. Nature is manifestation of God, and humanÃ¢â‚¬â€as part of itÃ¢â‚¬â€can expressthe manifestation into practical chains of religious worship and rituals. Addressing religious art of TadaoAndo with his Church of Water and RidwanKamilwith his Al-Irsyad Mosque, this paper aims to describe how ecology deals with religious architecture and how ecological standpoint fits toreligious rituals. This paper will also refer to the concept of deep ecology that traces connection to the wholeness, intuition, and affective perception of the sacredness and interconnection of all life. Simply, deep ecology tries to Ã¢â‚¬Å“resacralizeÃ¢â‚¬Â human perceptions of natural world.Keywords: Religious Architecture, Church, Mosque, Ecology, Nature.